HUBUNGAN DIABETES MILITUS DAN OBESITAS DENGAN KEJADIAN PREEKLAMSI PADA IBU HAMIL - Agustin, Leonita Dwi; Asta, Adesy; Prasasti, Dara Anggun (JOURNAL OF HEALTH SCIENCE, 2021)
Preeclampsia is a multisystem disorder with a complex etiology that usually occurs during pregnancy. Preeclampsia is usually defined as an increase in blood pressure and proteinuria that occurs after 20 weeks of gestation. This research is a quantitative research with an analytical survey with a cross sectional approach. The population in this study were all pregnant women who were treated totaling 99 pregnant women. The sample of this research used random sampling method. The sample of this study amounted to 40 respondents. Data analysis was carried out in two stages, namely univariate analysis and bivariate analysis with Chi-square statistical test. The results of bivariate analysis showed that there was a relationship between diabetes mellitus (p value = 0.00) and obesity (p value = 0.003) with the incidence of preeclampsia in pregnant women. Suggestions are expected for health workers to further improve the quality of health services by promoting health to pregnant women by providing counseling about the signs and dangers that can be caused by the incidence of preeclampsia in pregnant women. Keywords: Preeclampsia in pregnant women